Hypothalamic Kisspeptin Neurons Regulates Energy Metabolism and Reproduction Under Chronic Stress - Huang, Yinqiong; Liu, Qinyu; Huang, Guifeng; Wen, Junping; Chen, Gang (Frontiers in Endocrinology, 2022)
Background: Stress activates the hypothalamic-pituitary-adrenal (HPA) axis, affecting energy homeostasis and reproduction. The aim of this study was to investigate whether stress affected energy metabolism and reproduction through the glucocorticoid receptor on Kisspeptin neurons in the hypothalamus. Methods: Four groups included control group, chronic restraint stress group, Kisspeptin specific glucocorticoid receptor knock out group (KGRKO) and KGRKO+stress group. Body weight, food intake, estrous cycle of female mice, serum sex hormone levels, serum corticosterone and prolactin, Kisspeptin expression in the hypothalamus were measured. Results: The restraint stress group showed a significant weight loss compared with the control group. KGRKO+restraint stress group had a reduced weight loss, suggesting that restraint stress might partially affect the energy metabolism through GR on Kisspeptin neurons. In terms of reproductive function, the restraint stress group and the KGRKO+restraint stress group showed missing pre-estrus period or prolonged estrous cycles. Serum LH and FSH in KGRKO + restraint stress group decreased significantly compared with KGRKO group. However, no significant difference in the level of serum testosterone was observed. After restraint stress, the levels of serum cortisol and prolactin in male and female mice were significantly higher than the control group, and the hypothalamus Kiss1 gene mRNA expression and Kisspeptin protein expression were significantly decreased. Conclusion: Chronic restraint stress induced weight loss and negative changes in reproduction, which were partially mediated by glucocorticoid receptor on Kisspeptin neurons in the hypothalamus.